Original article (Folia Neuropathologica, 2011)

(untitled) - Sobaniec-Łotowska, Maria E.; Łotowska, Joanna M.
The objective of the current ultrastructural study was to explore the potentiality of the neuroprotective effect of TPM against damage of pyramidal neurons in the hippocampal CA1 and CA3 sectors in an experimental model of febrile seizures (FS) in rats. The FS group exhibited variously pronounced submicroscopic lesions of the neuronal perikarya, including total cell disintegration. Advanced changes induced by hyperthermic stress were manifested by marked degenerative abnormalities, such as substantial swelling of the mitochondria, dilation, degranulation and disintegration of the granular endoplasmic reticulum, and vacuolar changes in the Golgi complex. The most substantially damaged pyramidal neurons showed features of aponecrosis (so-called “dark neurons”), resulting in a marked neuronal loss in the explored areas of the hippocampal cortex. The neurodegenerative changes were accompanied by distinct damage to the blood-brain barrier components. The administration of topiramate at a dose of 80/kg b.m. prior to the induction of hyperthermic stress (as prevention against febrile seizures) caused a substantial neuroprotective action – the drug efficiently lightened the neuronal damage, basically reduced cell aponecrosis and enhanced cell viability. However, TPM applied directly after FS induction did not exert any distinct neuroprotective effect on the perikarya of pyramidal neurons in the hippocampal cortex.